Port performance in container transport logistics : a multi-stakeholder perspective - Ha, Min-Ho (2021)
This study proposes a measurement instrument for port performance in the context of container transport logistics (CTLs) by taking perspectives from different port stakeholders. An importance-performance analysis (IPA) is used to develop an analytical tool for investigating the importance and performance (IP) of major container ports in South Korea against individual CTLs criterion. The main originality of this study is the development of a measurement instrument to provide managerial and operational insights to both port managers (i.e. terminal operating companies) and policy makers (i.e. port authorities and government) for stakeholder management in CTLs. The analysis helps port managers and policy makers to converge the different objectives and concerns for better management.